Homogeneous and highly controlled deposition of low viscosity inks and application on fully printable perovskite solar cells. Issue 1 (31st December 2018) - Meroni, Simone M. P.; Mouhamad, Youmna; De Rossi, Francesca; Pockett, Adam; Baker, Jennifer; Escalante, Renán; Searle, Justin; Carnie, Matthew J.; Jewell, Eifion; Oskam, Gerko; Watson, Trystan M.
Abstract: The fully printed, hole-transporter-free carbon perovskite solar cell structure incorporating a triple mesoscopic layer has emerged as a possible frontrunner for early industrialisation. It is an attractive structure because it can be fabricated by the simple sequential screen printing and sintering of titania, zirconia, and carbon. The device is finalised by manual dropping of a perovskite precursor solution onto the carbon which subsequently infiltrates. This stage in device fabrication is inhomogeneous, ineffective for large areas, and prone to human error. Here we introduce an automated deposition and infiltration system using a robotic dispenser and mesh which delivers the perovskite precursor uniformly to the carbon surface over a large area. It has been successfully used to prepare perovskite solar cells with over 9% efficiency. Cells, prepared by this robotic mesh deposition, showed comparable performance to reference cells, made by standard drop deposition, confirming this approach to be effective and reliable. X-ray diffraction and Raman spectroscopy were used to confirm the uniformity of the deposition over a large area. Abstract :